Lack of secondary hyperparathyroidism in sub-group of vitamin D deficient postmenopausal women: Is VDR gene polymorphism behind this mystery?. Issue 1 (January 2022) - Dixit, Vivek; Tripathi, RL; Dhanwal, Dinesh Kumar
Abstract: Background and aims: We aimed to determine the cause of non-secondary hyperparathyroidism (Non-SHPT) in Indian postmenopausal women. Materials & methods: 334 apparently healthy postmenopausal women were assessed for bone mineral homeostaisis including Vitamin D, PTH and VDR polymorphism. Results: 83% of the subjects had vitamin D deficiency further associated with VDR gene polymorphism ( P 0.000). A sizable number of subjects (N = 83) did evoke SHPT despite low vitamin D levels. We observe that VDR gene polymorphism was strongly associated in the sub-group of non-SHPT. Conclusion: lack of SHPT warrants researchers to study the pathophysiology of non-SHPT in detail to substantiate our findings. Abstract : Context : In clinical practice, there are sub-groups of subjects in whom parathyroid hormone does not increase despite vitamin D deficiency! This phenomenon is poorly understood and remains a research question for clinicians & scientists.